Pathways from the (semi) Periphery: Early Assessment of EU Mercosur Trade Agreement in Principle: Environmental and Development Aspects - Nahtigal, Matjaz (American Journal of Trade and Policy, 2023)
In the current international and domestic context, imagining a more complex bilateral trade agreement is more accessible than between the European Union (E.U.) and Mercosur (the South American International Trading Bloc). The tensions between these major trading blocs only aggravate international trade and economic relations. Consequently, the World Trade Organization (WTO) is bracing for its most significant challenge since its establishment in 1994. Between the E.U. and Mercosur's complex trade agreement and the WTO's challenge, the post-COVID-19 international legal environment has become even more complicated.  The aims of this paper are: (1) to analyze the importance of the E.U.–Mercosur agreement within the current institutional trade framework; (2) to present some of the most controversial dilemmas posed by the present agreement; and (3) to evaluate the extent to which the agreement may support or hinder more sustainable and inclusive development among both trade partners. This study will focus on Brazil due to its geography, population size, and historical efforts to bring the nation closer to the international periphery and its radical turn to authoritarian populism. Additionally, Brazil's Amazon Rainforest's global necessity is essential for this study.
Keywords: Free Trade Agreements; Development Policy Space; Institutional Innovations; Inclusive and Sustainable Development; Protection of Public Goods; Variety of Models of Growth; Pathways from (semi) Periphery